Model Inovasi Perbankan Menuju Branchless Banking: Studi Kualitatif Adopsi Teknologi Berbasis Value Integrasi Schwart Value dan Utaut 2 - Marfiadi, Ahmad Hendra; Widyastuti, Sri; Shite, Mombang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The objective of this study is to explore customer values specifically value conversation, openness to change, self-enhancement, and self-transcendence in the use of mobile banking, based on the UTAUT2 framework. This is a qualitative study, employing Focus Group Discussions (FGDs) as the data collection method. Each value category is represented by 4 to 6 respondents, with participants confirmed to be willing to join the FGD sessions. The findings indicate that mobile banking is more likely to be accepted by users when the app’s features and design are aligned with their core values. For conservative users, strong security features and a simple user interface are more appealing. Conversely, users with openness values are more attracted to innovative, flexible, and customizable features. Features that enable social contributions attract users who value self-transcendence, while those oriented toward self-enhancement are drawn to features that support efficient personal financial management.